All Days 1997
DOI: 10.2118/37273-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Formation Calcium on the Effectiveness of Generically Different Barium Sulphate Oilfield Scale Inhibitors

Abstract: One of the most common methods of preventing downhole and topside mineral scale formation in oilfields is through the use of chemical scale inhibitors. Several aspects of the brine composition may affect the performance of the various scale inhibitors used in oilfield applications and, in this paper, we will focus on the role of calcium ion concentration. The calcium concentration in a particular reservoir and in the inhibitor slug, often determines the extent to which the inhibitor species is retained in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…The conclusions from this work, however, are quite different from those of Hennessey et al [6] in that the presence of calcium and additives together appear to promote rather than inhibit nucleation. This work also supports the previous studies of Benton et al [3] and Graham et al [5]. In particular, the differences observed by Graham et al for the various additives could be due to the differences in complexation strength with calcium.…”
Section: Article In Presssupporting
confidence: 91%
See 2 more Smart Citations
“…The conclusions from this work, however, are quite different from those of Hennessey et al [6] in that the presence of calcium and additives together appear to promote rather than inhibit nucleation. This work also supports the previous studies of Benton et al [3] and Graham et al [5]. In particular, the differences observed by Graham et al for the various additives could be due to the differences in complexation strength with calcium.…”
Section: Article In Presssupporting
confidence: 91%
“…It should be noted that most literature where an effect of calcium has been observed (with inhibitor present) was conducted at relatively high concentrations [3][4][5] ($25 mM Ca 2þ ). We chose a relatively low calcium concentration but high enough to affect both conductivity and nephelometry significantly: the concentration chosen was $1.3 mM Ca 2þ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the MIC for barite prevention in a given brine mix increases with SR. It has also been found that the presence of calcium (Ca 2þ ) generally helps phosphonate SIs to inhibit barite, whereas the presence of magnesium (Mg 2þ ) tends to reduce their IE (Graham et al 1997(Graham et al , 2003Boak et al 1999). In this work, we have found that the MIC level of selected phosphonate SIs is controlled mainly by the SR, and these are denoted as Type 1; however, the MIC of other phosphonate SIs is controlled mainly by brine [Ca 2þ ] and [Mg 2þ ] content, and these are denoted as Type 2.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It is also a simple crystallization system without complications from the presence of polymorphs that has been useful as a model for theoretical and laboratory experimental studies. [4][5][6][7] Phosphonate additives are often used to inhibit either nucleation or growth of barium sulfate in order to avoid scale formation 5 and several studies have shown that a complex relationship between structure, functional groups, and ionization state of the phosphonate additive impacts on this inhibition.…”
Section: Introductionmentioning
confidence: 99%